The highest region of muscle spindle abundance should be the optimal target of botulinum toxin A injection to block muscle spasms in rats - Yu, Jie; Li, Yunshan; Yang, Lu; Li, Yi; Zhang, Shibin; Yang, Shengbo (Frontiers in Neurology, 2023)
Purpose: The effective relief of muscle spasticity requires prompt solutions in rehabilitation medicine. This study aimed to reveal that the highest region of muscle spindle abundance is the optimal target of botulinum toxin A (BTX-A) injections for blocking muscle spasm. Methods: Sixty adult, male Sprague–Dawley rats with lower limbs spasm caused by stroke after modeling,weighing (200 ± 20) g, were included in this study. The modelrats were divided into four groups: muscle spasm model group (group A), model rats treated with BTX-A injections into the middle of the muscle belly (group B), model rats treated with BTX-A injections into the centre of the intramuscular nerve-dense region (INDR) (group C), and model rats treated with BTX-A injection into the centre of the highest region of muscle spindle abundance (HRMSA) (group D). Groups B, C, and D were further divided into two subgroups: the 3rd and 6th days after BTX-A injection. The rats in each group were assigned Ashworth scale scores, and the changes in gastrocnemius muscle tension, wet muscle weight, and cross-sectional area of muscle fibrewere detected. Results: Muscle spindle abundance was the highest in the upper part of the INDR. Group B experienced no significant changes in Ashworth scale scores, muscle tension, wet muscle weight, or cross-sectional area of the muscle fibre. Conversely, groups C and D experienced a decrease in these indicators. Group C experienced the most significant decrease in wet muscle weight and cross-sectional area of muscle fibres. Group D experienced the most notable decrease in Ashworth scores and muscle tension. There were no significant differences in the indicators between the 3rd and 6th days after BTX-A injections in group B andthere weresignificant differences in the improvement in the indicators between the two subgroups in groups C and D, with group D experiencing more notable intersubgroup differences. Conclusion: The efficacy of BTX-A injections into the HRMSA is significantly superior to that of conventional BTX-A injections into the middle of the belly muscle or the INDR in the treatment of muscle spasms. Hence, HRMSA should be the optimal target of BTX-A to block muscle spasms.